Learning from failure feedback for subsequent task performance: A matter of personality? - Thiel, Katharina; Semrau, Thorsten (Frontiers in Psychology, 2022)
The present study expands our knowledge of the differential consequences of failure feedback. Spe-cifically, we conducted an online experiment to elaborate on how conscientiousness and extraver-sion contribute to explaining whether individuals learn from failure feedback for future task per-formance. In line with our hypotheses, we find that individuals who are highly conscientious and/or highly extraverted are more likely to learn from failure feedback than their counterparts. We dis-cuss the implications of our study and derive practical implications.